1999
DOI: 10.1088/0741-3335/41/10/101
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt in time and wide in space variations of heat diffusivity during ITB formation in JT-60U reverse shear discharges

Abstract: New features of the space-time evolution of the internal transport barrier (ITB) were highlighted during recent JT-60U reverse shear (RS) experiments. An ITB evolution in RS plasmas is often a combination of the fast time-scale processes and the gradual ones. Fast time-scale processes are the common intrinsic features of JT-60U RS plasmas and are seen as the simultaneous (within a few milliseconds) rise and decay of electron temperature (T e ) on two zones separated by a region without variation of T e . The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…The reason or condition of such a double jump has not yet been clarified, but this observation suggests the existence of multiple stages (or structures) of transport in the box type ITB regime. In JT-60U we have observed a so called 'ITB event' [38] which is characterized by abrupt and spatially wide (covers 30% The to big circles at n e /n GW~0 .7 corresponds to a pellet injected discharge and a reference gas fuelled discharge shown later in Fig. 15.…”
Section: Response Of Itb To Heating and Momentum Inputmentioning
confidence: 99%
“…The reason or condition of such a double jump has not yet been clarified, but this observation suggests the existence of multiple stages (or structures) of transport in the box type ITB regime. In JT-60U we have observed a so called 'ITB event' [38] which is characterized by abrupt and spatially wide (covers 30% The to big circles at n e /n GW~0 .7 corresponds to a pellet injected discharge and a reference gas fuelled discharge shown later in Fig. 15.…”
Section: Response Of Itb To Heating and Momentum Inputmentioning
confidence: 99%
“…One possible explanation is based on the reduction of the turbulent viscosity due to E × B velocity shear, resulting in a localized jet of E × B flow (Staebler 2000). Staebler (2000) no special role is attributed to rational q values, many experiments suggest, that, in the presence of an evolving current profile, ITB transitions are triggered, when low order rational q values emerge as q 0 or q min decrease (Koide et al 1994, Bell et al 1996, Greenfield et al 1999, Neudatchin et al 1999, Joffrin et al 2001, Günter et al 2001a, Joffrin et al 2002a. Although different in its appearance, further evidence for a link between transport and rational q values is given by the RTP results (figure 12 in section 2.3.1), which describe the electron heat transport by the coexistence of a multitude of transport barriers in the proximity of rational q-surfaces (Hogeweij et al 1998).…”
Section: Internal Transport Barrier Formation and Sustainmentmentioning
confidence: 99%
“…where Φ : Σ × R n −→ R n , c : Σ × Ω −→ R, b : I × Ω −→ R n , and u : Σ × Ω −→ R. The function Φ satisfies the following properties: There exist two countably additive bounded nonnegative measures γ (·), β(·) ∈ M + c (Σ) (not necessarily nonatomic) and nonnegative constants c 1 , c 2 such that (1) …”
Section: An Examplementioning
confidence: 99%
“…First is theoretical; the author has studied evolution equations determined by linear operator valued measures and this is an attempt to generalize such studies to nonlinear operator valued measures. The second is physical; in the study of plasma [1] dynamics, thermodynamics and material sciences, it has been observed by scientists that under certain physical situations diffusion coefficient (or conductivity) may exhibit dramatic change in an extremely short period of time. Similarly, in population studies [2] abrupt change of diffusion coefficient including drift may occur due to shock leading to sudden and possibly chaotic dispersal of $ WCNA-2008, Orlando, July 2-9, 2008.…”
Section: Introductionmentioning
confidence: 99%